2011
DOI: 10.1590/s0100-67622011000600001
|View full text |Cite
|
Sign up to set email alerts
|

Estrutura genética em microescala espacial de Myrcia splendens (Myrtaceae)

Abstract: 4RESUMO -Em ecossistemas fragmentados, comuns no sul de Minas Gerais, os corredores de vegetação são elementos de grande importância ecológica para o fluxo gênico. Os corredores de vegetação na região de Lavras, MG, são estreitos (entre 3 e 6m), de vegetação secundária formada pela colonização de valas e interligam fragmentos remanescentes de vegetação primária. Nestes dois ambientes, é comum a ocorrência da espécie Myrcia splendens, que produz frutos de dispersão zoocórica. Objetivou-se, neste trabalho, a ava… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
13
1
4

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 26 publications
4
13
1
4
Order By: Relevance
“…There was significant genetic differentiation (P < 0.000) between populations. This variability distribution pattern was different from that found in studies on other species of tropical plants (Rossi, 2007;Rossi et al, 2009;Bertoni et al, 2010;Brandão et al, 2011). However, the same distribution pattern between populations was found in a study carried out by Silva et al (2007), who found high inter-population genetic differentiation between populations of Oryza glumaepatula Steud.…”
Section: Genetic Differentiation Between Populationscontrasting
confidence: 82%
See 2 more Smart Citations
“…There was significant genetic differentiation (P < 0.000) between populations. This variability distribution pattern was different from that found in studies on other species of tropical plants (Rossi, 2007;Rossi et al, 2009;Bertoni et al, 2010;Brandão et al, 2011). However, the same distribution pattern between populations was found in a study carried out by Silva et al (2007), who found high inter-population genetic differentiation between populations of Oryza glumaepatula Steud.…”
Section: Genetic Differentiation Between Populationscontrasting
confidence: 82%
“…Therefore, this method is efficient to detect genetic variability within and between populations of T. subincanum. The usefulness of this type of marker has been previously described for both cultivated and wild species (Rossi et al, 2009;Almeida et al, 2009;Brandão et al, 2011). This marker also presents high reproducibility and potential to be used in species without detailed DNA sequence information (Rossi et al, 2009;Almeida et al, 2009;Brandão et al, 2011).…”
Section: Issr Analyses and Genetic Diversity Within Populationsmentioning
confidence: 99%
See 1 more Smart Citation
“…ISSR markers have been used to study the population structure of Myrtaceae species by various authors. Brandão et al (2011) used ISSR markers to study Myrtaceae species and observed seven to eleven polymorphic loci per primer, similar to the results of our study.…”
Section: Issr Marker Analysissupporting
confidence: 86%
“…Oliveira et al (2014), evaluating the genetic distance among 37 accesses of Psidium spp., using 17 primers, obtained 216 polymorphic fragments, with an average of 13 by primer. Studying the diversity of 272 genotypes of the same species of the jaboticabeira family, Myrcia splendens (SW), Brandão et al (2011) used 10 primers and identified 70 polymorphic fragments. Mani et al (2011), evaluating the genetic distance among 15 species of Psidium spp., used 31 ISSR primers and obtained a total of 234 polymorphic fragments.…”
Section: Polymorphism and Discriminatory Power Of Issr Primersmentioning
confidence: 99%